MSME Product Management Strategy from the â€œMerdeka Campusâ€ Program, Digital Design Production at BINUS University - Sonia, Candy (SEEIJ (Social Economics and Ecology International Journal), 2023)
The implementation of the â€œMerdeka Campusâ€ or independent campus is a program that prepares the best generation in Indonesia with a comprehensive career preparation program. This program is held by the Ministry of Education, Research and Technology. This program is a moment in carrying out research aimed at developing MSME products through independent learning class activities that will be held in 2022 (Odd Semester 2022-2023), which will consist of students from the Computer Science and Information Systems major who study visual communication design, especially in product design. The method used 3 stages of data validation, first by looking at the material presented in the syllabus and learning outcomes for 1 semester. Then it was developed with content validation for the prototype from the results of the questionnaire which determined the perfume product with logo design, packaging, aroma and price. Then enter the market validation stage by studying similar products at market selling prices. The result is a new method of determining technically feasible products that can meet user needs and business goals. MSME product development materials are no longer carried out over a long period of time, but can be carried out in 1 semester, including the ideation process, prototype to market validation.